Economic Impact Assessment of Climate Change: A Multi-gas Investigation with WIAGEM-GTAPEL-ICM - Claudia Kemfert; Truong Phuoc Truong; Thomas Bruckner (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
Climate change is a long-term issue due to the long lifespan of greenhouse gases and the delayed response of the climate system. This paper investigates the long-term economic consequences of both climate change impacts and mitigation efforts by applying the multiregional, multi-sectoral integrated assessment model WIAGEM based on GTAP-EL coupled with the reduced-form multi-gas climate model ICM. We investigate emissions reduction paths to reach a radiative forcing target of 4.5 w /m^2. Economic impacts are studied and compared with and without the inclusion of all GHG gases. We find that multi-gas emissions reduction causes less economic losses compared with a case where only CO2 emissions reductions would be considered.
Keywords: 330